Can appreciation be expansionary? Evidence from the euro area. (28th March 2018) - Lane, Philip R; Stracca, Livio
SUMMARY: We identify exogenous effects of shifts in effective exchange rates for euro area (EA) countries between 1999 and 2016. The identification strategy is based on an external instrument built on the assumption that movements in the euro nominal effective exchange rate are largely exogenous for individual EA countries once we control for EA aggregates. We find that a real appreciation creates a trade-off between expenditure switching (contractionary) and terms of trade (expansionary) effects, with the latter prevailing in most countries. We also find some heterogeneity in the way movements in the euro exchange rate are transmitted within the EA, in particular between 'core' and 'peripheral' countries, although differences are mostly not statistically significant.